Label-Free Surface-Enhanced Raman Scattering for Genomic DNA Cytosine Methylation Reading - Kazi Morshed Alom; Anastasiia Tukova; Nana Lyu; Alison Rodger; Yuling Wang (Molecules)
DNA methylation has been widely studied with the goal of correlating the genome profiles of various diseases with epigenetic mechanisms. Multiple approaches have been developed that employ extensive steps, such as bisulfite treatments, polymerase chain reactions (PCR), restriction digestion, sequencing, mass analysis, etc., to identify DNA methylation. In this article, we report a facile label-free surface-enhanced Raman scattering (SERS) spectroscopy system that utilizes gold nanoparticles (AuNPs) for signal enhancement of methylated DNA. The key innovation of this work is to use anionic nanoparticles at a high ionic strength to introduce the aggregation of AuNPs with anionic DNA. When target methylated DNA is present, the presence of a methyl group in the cytosine C5 position of CpG sites induces a Raman peak at 1350 cm−1. Our amplification-free system has a limit of detection (LOD) of 5% and a limit of quantification (LOQ) of 16% with good specificity. The method was applied to determine the hypermethylated levels of the germline of colorectal cancer cell lines SW48 and SW480. Our simple label-free method holds the potential to read the disease-associated methylation of genomic DNA.